Efektivitas Pelayanan Penanggulangan Kekerasan Anak pada Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kota Palembang - Wagisri, Wagisri; Pusnita, Indah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2022)
The purpose of this study was to determine the effectiveness of services to overcome child violence by the Integrated Center for Women and Children Services (P2TP2A) Palembang City. The research design used descriptive qualitative, the method used was observation, interviews and documentation. The informants in this study were the Head of UPT P2TP2A with one staff/employee who was directly involved in solving cases at UPT P2TP2A Palembang City, secretary, head of division, counselor and three children victims of violence and one adult woman at UPT P2TP2A Palembang City. The analysis technique used is data reduction, data presentation and conclusion drawing. The results of the research on the effectiveness of child violence prevention services by P2TP2A Palembang City stated that currently it was running well although there were several obstacles in overcoming the problem. However, legal assistance and coordination with related parties are able to solve the problems that occur in the community. This means that the family or victim who wants to make a report regarding cases of violence against children will be followed up immediately through P2TP2A assistance and in collaboration with applicable legal entities. The conclusion of the study shows that the service for overcoming child violence by P2TP2A Palembang City has not been effective based on the achievement of goals, integration and adaptation.